Iron assimilation and utilization in anaerobic ammonium oxidizing bacteria. (April 2017) - Ferousi, Christina; Lindhoud, Simon; Baymann, Frauke; Kartal, Boran; Jetten, Mike SM; Reimann, Joachim
Graphical abstract: Highlights: Anammox bacteria only assimilate ferrous iron. The Ahb pathway produces heme b in anammox bacteria. Individual systems may mature periplasmic and anammoxosomal cytochromes c . The Nif system is the only identified system for Fe–S protein assembly in anammox. The fate of iron inside the anammoxosome is unknown. Abstract : The most abundant transition metal in biological systems is iron. It is incorporated into protein cofactors and serves either catalytic, redox or regulatory purposes. Anaerobic ammonium oxidizing (anammox) bacteria rely heavily on iron-containing proteins – especially cytochromes – for their energy conservation, which occurs within a unique organelle, the anammoxosome. Both their anaerobic lifestyle and the presence of an additional cellular compartment challenge our understanding of iron processing. Here, we combine existing concepts of iron uptake, utilization and metabolism, and cellular fate with genomic and still limited biochemical and physiological data on anammox bacteria to propose pathways these bacteria may employ.